PENDIDIKAN ISLAM KRITIS-TRANSFORMATIF (STUDI KASUS PADA FRONT NAHDLIYIN UNTUK KEDAULATAN SUMBER DAYA ALAM (FNKSDA) MALANG) - Hayyik Ali Muntaha Mansur (Turatsuna : Jurnal Keislaman dan Pendidikan, 2019)
This study examines critical-transformative Islamic education on  Front Nahdliyin untuk Kedaulatan Sumber Daya Alam (FNKSDA). The FNKSDA was chosen because this organization has movement principles based on the Islamic Ahlusunnah wal Jamaah which interpreted progressively. This organization also combines Islamic studies with critical theories. In addition to conducting advocacy and research, FNKSDA also concerned with public education. Critical-transformative Islamic education is also important to study given the frequent absence of Islam or specifically Islamic education in responding to the problems of the lower classes of society.The focus in this study is three parts. First, how is the planning of Critical-transformative Islamic Education in the Nahdliyin Front for Sovereignty of Natural Resources (FNKSDA)? Second, How is the Implementation of Critical-Transformative Islamic Education in the Nahdliyin Front for Sovereignty of Natural Resources (FNKSDA)? And the last, how is the monitoring and evaluation of Critical-transformative Islamic Education in the Nahdliyin Front for Sovereignty of Natural Resources (FNKSDA)?This study uses a qualitative approach to the type of case study research. The research paradigm is a critical paradigm. Research data in the form of written text and oral text. The collection of data through interviews with informants, observations, and study documents. Data were analyzed using the constant comparative method. The data that researchers have obtained will be reduced or sorted, then categorized and analyzed.